Packaging and storage of sulfited and unsulfited coconut flour - Arabia, Ma. Janesa B. (1993)
The study was undertaken with the main objective of determining the effectivity of sodium metabisulfite as a pre-treatment for coconut flour. Dessicated coconut from Sirawan Food Coorporation was pasteurized in 0.200% sodium meatbisulfite solution for 10 minutes at 82 to 90°C. In the first phase, the equilibrium moisture contents of the unsulfited and sulfited coconut flours were determined by exposing the samples to different saturated salt solutions. The resulting sigmoid curves show that both products are most stable between 11% and 60% relative humidity conditions at 28 - 32°C. Maximum hygroscopicity of both products tend to develop at relative humidities above 62%. However, the sorption isotherm curve of the unsulfited coconut flour was higher indicating greater hygroscopicity. In the second phase the critical; moisture content was found to be 8.94% (dry basis) for the unsulfited coconut flours and 9.3% (dry basis) for the sulfited coconut flour. After 35 days of accelerated storage conditions, results showed a peroxide value of 8.92 meq per kg fat, free fatty acid of 0.68% and the yeast and mold count of 19 colonies per gram sample for the unsulfited coconut flour. For the sulfited coconut flour, after 35 days of storage, the peroxide value was 7.64 meq per kg fat, free fatty acid was 0.53% and with a yeast and mold count of two colonies per gram. The shelf life values of both products in 0.003 inch and 0.004 inch LDPE were calculated using the Half-Value Period Method. Using the 0.003 LDPE, the shelf-life of the unsulfited coconut flour was established to be 530 days, and the sulfited coconut flour, 885 days. The 0.004 inch LDPE gave a shelf-life of 645 days for the unsulfited coconut flour and 1035 days for the sulfited coconut flour. Results of the study showed that pre-treatment with 0.200% sodium metabisulfite was effective in improving the storage characteristics and prolonging the shelf life of the coconut flour